2007
DOI: 10.1146/annurev.publhealth.28.021406.144020
|View full text |Cite
|
Sign up to set email alerts
|

Community Factors in the Development of Antibiotic Resistance

Abstract: The global impact of antibiotic resistance is potentially devastating, threatening to set back progress against certain infectious diseases to the preantibiotic era. Although most antibiotic-resistant bacteria originally emerged in hospitals, drug-resistant strains are becoming more common in the community. Factors that facilitate the development of resistance within the community can be categorized as behavioral or environmental/policy. Behavioral factors include inappropriate use of antibiotics and ineffecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
85
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(86 citation statements)
references
References 75 publications
0
85
0
1
Order By: Relevance
“…The faecal carriage of ESBL-producing Enterobacteriaceae in asymptomatic Thai individuals is close to or sometimes higher than the prevalence of ESBL-producing bacteria in clinical isolates collected from patients in Thailand (30-48 % in 2005-2007Hawser et al, 2009;Kiratisin et al, 2008b). Lactamases belonging to CTX-M group I (20 %) and IV (77 %) were predominant among the 164 CTX-M b-lactamases identified in asymptomatic individuals; this pattern is identical to that of patient isolates in Thailand, where CTX-M-14 (group IV) and CTX-M-15 (group I) were the ESBLs mainly responsible for resistance in E. coli (Kiratisin et al, 2008a;Niumsup et al, 2008).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The faecal carriage of ESBL-producing Enterobacteriaceae in asymptomatic Thai individuals is close to or sometimes higher than the prevalence of ESBL-producing bacteria in clinical isolates collected from patients in Thailand (30-48 % in 2005-2007Hawser et al, 2009;Kiratisin et al, 2008b). Lactamases belonging to CTX-M group I (20 %) and IV (77 %) were predominant among the 164 CTX-M b-lactamases identified in asymptomatic individuals; this pattern is identical to that of patient isolates in Thailand, where CTX-M-14 (group IV) and CTX-M-15 (group I) were the ESBLs mainly responsible for resistance in E. coli (Kiratisin et al, 2008a;Niumsup et al, 2008).…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, several studies have linked the high prevalence of antibiotic-resistant bacteria in the human population to the use of antibiotics in the farming industry (Bailar & Travers, 2002;Dutil et al, 2010;Hawkey & Jones, 2009;Larson, 2007). Recent studies have revealed an increased prevalence of ESBL-producing micro-organisms in poultry at chicken farms (Briñas et al, 2005;Yuan et al, 2009).…”
Section: -O Luvsansharav and Othersmentioning
confidence: 99%
“…Over the last decades, antibiotic overuse and misuse have largely contributed to the emergence of multidrug-resistant (MDR) pathogens by exerting a selective pressure on microorganisms present in the environment (24,38). Independent of infection control measures, carefully considered antibiotic usage has proved to be highly beneficial in reducing the emergence of resistance (23,33).…”
mentioning
confidence: 99%
“…Two simulated endocardial vegetations (total of four) were removed at 0, 4,8,24,32,48,56, and 72 h for days 0 to 3 and 0, 4, 8, 24, 32, 48, 56, 72, and 96 h for days 4 to 8. The SEVs were homogenized, diluted in cold normal saline, and plated onto TSA plates to allow colony counting.…”
mentioning
confidence: 99%
“…This unfavorable situation is further aggravated by a shortage of new classes of antibiotics with novel modes of action that are essential to contain the spread of antibiotic -resistant pathogens (Livermore 2004 ). In fact, some infectious disease experts have expressed concerns that we are returning to the pre -antibiotic era (Larson 2007 ). Therefore, there is an urgent need to develop novel antibacterial agents to eliminate multidrug -resistant bacteria (Breithaupt 1999 ).…”
Section: Introductionmentioning
confidence: 99%